Philippines : Financial Sector Assessment Program-IOSCO Objectives and Principles of Securities Regulation Assessment. (IMF Staff Country Reports; Country Report ;, 2004)
This report reviews the Financial Sector Assessment Program of the Philippines on International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation. The report was prepared by a staff team of the International Monetary Fund and the World Bank as part of the Financial Sector Assessment Program for the Philippines. It assesses the effectiveness of securities regulation, soundness of market intermediaries, and development prospects for the capital markets, including observance of the IOSCO Objectives and Principles of Securities Regulation.